Historical Monuments of Gulluk Village of Qakh Region - Memmedli, Akif; Sultanov, Ələddin (Scholarya Demo Journal of Ruby, 2021)
With its ancient history, ethnic richness, and monuments of various religions, northwestern region of Azerbaijan is a model of tolerance. The Qakh region is an important part of the region. As a result, our article was based on ethnographic research and field materials gathered in the Qakh region's Gulluk village. The passage of time and the introduction of new religions into people’s lives such as Christianity and, finally, Islam brought with them a slew of innovations and positive changes. In general, the presence of numerous Albanian-Christian temples and mosques in northwestern region of Azerbaijan demonstrates this as well. Gulluk village has a long history, and the majority of its residents are Azerbaijani Turks, Sahurs, and Gypsies. The article reflected the ethnographic features and history of the village. During the research, data on the ethnic characteristics, customs, and agriculture of the rural population were gathered. Among the places of worship associated with pre-Islamic religions in the study area, Albanian Christian temples predominate. These historical monuments were sometimes destroyed by accident, sometimes on purpose, and sometimes subjected to specific destruction. During the investigation of pre-Islamic monuments, the remains of the Fairy Tower temple, a temple, and an Albanian temple were examined. The Friday (Juma) mosque, cemeteries, ancient buildings, and stone inscriptions were all inspected while inspecting Islamic monuments in the village of Gulluk. At the same ttime, the acquired manuscripts were studied in order to determine who was historically involved in religious activities.